New spaces of new speaker profiles: Exploring language ideologies in transnational multilingual families. (3rd August 2017) - Soler, Josep; Zabrodskaja, Anastassia
Abstract: This article looks at Spanish-Estonian speaking families and their language ideologies in relation to language use in the family setting—how parents decide to use languages among themselves and with their children. Family members choose different languages for different purposes when they talk to one another. In our study, parents draw on their knowledge of the 'one parent–one language' strategy but also translanguage for different reasons, constructing new patterns of bilingual modes. In the article, we examine parents' attitudes towards language maintenance, transmission, and use with their children. We incorporate the lens of 'new speaker' research to analyse the empirical data collected in Tallinn households among Spanish-Estonian speaking families so as to contribute to a better understanding of family language policy, planning, and management, highlighting how macro-level sociolinguistic expectations and norms might be elaborated on the micro level in everyday social interactions. (Family language policy, language ideology, new speakers, Estonian, Spanish)*